3D Printed Supercapacitor: Techniques, Materials, Designs, and Applications. (1st November 2022) - Li, Mengrui; Zhou, Shiqiang; Cheng, Lukuan; Mo, Funian; Chen, Lina; Yu, Suzhu; Wei, Jun
Abstract: Supercapacitors (SCs) offer broad possibilities in the rising domain of military and civilian owing to their intrinsic properties of superior power density, long lifetime, and safety features. Despite of low‐cost, facile manufacture, and time‐saving, 3D printing technology unleashes the potential of SCs in terms of achieving desirable capacitance with high mass loading, fabrication of well‐designed complicated structures, and direct construction of on‐chip integration systems. In this review, first, the representative printing technologies for SCs and advanced printable materials are scrutinized for SCs and advanced printable materials. Then the structure design principles of electrodes and devices are respectively highlighted and reported cases are systematically summarized. Next, configurations of the SCs and their applications in various areas are described in detail. Finally, the promising research directions for the future are discussed. The perspectives reviewed here are expected to provide a comprehensive understanding of 3D‐printed SCs and guidance in realizing their promise in various applications. Abstract : 3D printing technology provides new opportunities for the rapid preparation of supercapacitors with optimum structure and higher performance. This article provides a comprehensive review of recent developments in 3D printing techniques, printable modules, and relevant designing strategies for fabricating supercapacitors. The limitations of current 3D printing technologies and existing challenges, and promising research directions in the future are discussed.